ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL KOMUNIKASI MATEMATIS MATERI BANGUN RUANG - Iffa Hanifah Rahman; Meilinda Manda Yassar; Nadya Suciati Fauziah; Nurul Rohmi; Hamdan Sugilar (Jurnal Perspektif, 2019)
The purpose of this study is to describe the errors and causes that often occur in solving problems in the material building space beam and cube in terms of mathematical communication. In this study using a type of qualitative descriptive research, with data collection techniques used are tests, and interviews. The subjects of this study were 4th semester students at one of the universities in Bandung. The analysis technique used is an interactive technique which includes data collection, data reduction, data presentation, and conclusion drawing. The mathematical communication indicators used in this research are expressing everyday problems in mathematical languages / symbols, presenting allegations, and drawing conclusions. Errors made by students in solving problems are wrong in symbolizing data that is known and asked, does not calculate prerequisite data, determine formulas, and do not draw conclusions. The cause of the error is due to the assumption that symbolizing the known and asked data is not important, does not focus when working on the problem so that it is not thorough and understands the questions given, and the unfamiliarity to draw conclusions on each problem resolved